EKSPRESI ESTRUS DOMBA LOKAL PALU YANG DIBERIKAN KONSENTRAT - Ridwan, Ridwan (AgriSains, 2005)
The study was to investigate the addition of concentrate on the sign of estrus and estrus dinction local ewe. The sign of estrus was discovered to be significantly better on ewe given concentrate for 17 days than on those given concentrate for 7 days. Key words: Concentrate, estrus, local sheep.